Cable-Driven Exoskeleton for Ankle Rehabilitation in Children with Cerebral Palsy - Iñaki Dellibarda Varela; Pablo Romero-Sorozabal; Gabriel Delgado-Oleas; Jorge Muñoz; Álvaro Gutiérrez; Eduardo Rocon (Applied Sciences, 2025)
Cerebral palsy is the leading cause of motor disability in early childhood, with no curative treatment currently available. To mitigate its effects and promote motor rehabilitation, robotic-assisted therapies have emerged as a complement to conventional physiotherapy. In particular, cable-driven exoskeletons offer notable advantages, providing patients with additional mobility and interaction with their environment while preserving motion assistance. Within this context, the Discover2Walk project introduces a modular cable-driven robotic platform designed for early-stage gait rehabilitation. This article presents a novel ankle control module capable of actuating 3 degrees of freedom: 2 translational (in the x and z directions) and 1 rotational (dorsiflexion/plantarflexion). Experimental results confirm the technical feasibility of the approach and its effectiveness in guiding motion within the targeted degrees of freedom.